PowerPoint-Based Guessing Games on Wild Animals Theme to Enhance Speaking Skills of Group B Children at RA ATTA'LIM Sungai Duo - Yulia, Wina; Sunimaryanti, Sunimaryanti; Andre, Lesis; Syam , Fadhli (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
The problem addressed in this study is that in Group B of RA ATTA’LIM Sungai Duo, children's language development, especially in speaking skills, had not developed optimally. This was indicated by children not speaking fluently or correctly, having difficulty expressing ideas verbally, and possessing limited vocabulary during the learning process both with teachers and peers. The purpose of this study was to analyze whether PowerPoint-based guessing games on the theme of wild animals could improve the speaking skills of Group B children.The type of research is descriptive qualitative. The place schedule was from February 24 to April 14 in RA ATTA’LIM sungai duo. The research instruments were observation, interviews, and documentation. The primary data consisted of 16 children from group B and 3 teachers, while secondary data were used to support the research. Data collection techniques included observation, interviews, and documentation. The data analysis techniques involved data reduction, data presentation, and drawing conclusions. The data validity technique used was triangulation.The research results show that the language game guessing games based on PowerPoint with the theme of wild animals has a positive impact on improving the speaking skills of Group B children. (1) The implementation of the PowerPoint-based guessing games with the theme of wild animals is in accordance with the indicators based on Wibowo & Suyadi’s theory (2021:10). (2) The speaking ability of Group B children at RA ATTA'LIM Sungai Duo before the implementation of the PowerPoint-based guessing games with the theme of wild animals was relatively low, as indicated by several children being at the “Not Yet Developed (BB)” level. (3) There was an improvement in the speaking skills of Group B children at RA ATTA'LIM Sungai Duo after implementing the PowerPoint-based guessing games with the theme of wild animals. In Meeting 1, MB reached 68 %, Meeting 2 reached 81%, and Meeting 3 reached 93%. Thus, it can be concluded that PowerPoint media and the guessing games approach have proven effective in stimulating language development in early childhood, particularly in speaking skills.